Creation of UI Design Prototype Mobile App Textile Museum to Increase The Number of Visitors, Tourism Marketing and Brand Awareness - Arief Yulianto (Jurnal Syntax Admiration, 2023)
Textiles are an important part of Indonesia, both as a component of clothing and as ritual and ceremonial items. The Textile Museum is a museum founded in 1976 which was pioneered by Mr. Ali Sadikin as the governor of DKI Jakarta at that time. However, over time, interest in visiting museums has decreased, especially with the C19 pandemic, many learning tourist attractions such as museums have experienced a decline in visitors. The role of the mobile app interface can make it easier for visitors or potential visitors and anyone to get various information easily and practically. This research will create a prototype UI design mobile apps interface for the Textile Museum using Adobe XD software. The research begins with mapping the problem, determining various solutions, determining the best solution, forming prototypes, and testing the results on target consumers, testing marketing concepts and brand awareness to capture the number of visitors to come to the Textile Museum.